Leadership - Neider, Linda L., 1953-; Schriesheim, Chester (Research in management., 2002)
The primary mission of the series is to disseminate and advance knowledge in the field of management, broadly defined. As such, topics include traditional areas of management such as planning, controlling, leading, and organizing, as well as related disciplines.